Beyond Monetary Barriers to Electric Vehicle Adption: Evidence from Observed Usage of Private and Shared Cars - Wolfgang Habla; Vera Huwe; Martin Kesternich (Philipps-University Marburg, School of Business and Economics, 2020)
We use car-level micro data to provide empirical evidence on the usage of conventional and electric vehicles (EVs) in private and car sharing fleets in Germany. We shed light on both monetary and non-monetary barriers to EV adoption and usage by exploiting the feature that variable costs are identical for shared vehicles but different for private car owners across engine types. While drivers respond to monetary incentives when using conventional cars, this does not hold for EVs. We find that EVs are, on average, driven shorter distances than conventional vehicles, both in terms of annual and single-day mileage, even if costs are identical. We also document that car sharing intensifies the usage of conventional cars but not that of EVs.
Keywords: R41; D12; Q50; 330; Electric vehicles; internal combustion engine vehicles; barriers to adoption; cruising range; driving patterns; car sharing; range limitations; range anxiety